Comparing Time Efficiency of Sprint vs. High-Intensity Interval Training in Reducing Abdominal Visceral Fat in Obese Young Women: A Randomized, Controlled Trial - Tong, Tomas K.; Zhang, Haifeng; Shi, Hongru; Liu, Yang; Ai, Jingwen; Nie, Jinlei; Kong, Zhaowei (Frontiers in Physiology, 2018)
High-intensity interval training (HIIT) is an emerging lifestyle intervention strategy for controlling obesity. HIIT consisted of brief all-out supramaximal sprint intervals was termed as sprint interval training (SIT). This study was designed to examine the time-efficient characteristics of SIT in reducing abdominal visceral fat. Methods: A randomized controlled trial was conducted to compare the specific adaptations of SIT (80 x 6-s all-out cycle sprints interspersed with 9-s passive recovery) with those resulting from a HIIT regimen with training volume relatively higher (repeated 4-min bouts of cycling at 90% V̇O2max alternated with 3-min rest, until the work of 400KJ was achieved), and with those of nonexercising control counterparts (CON). Forty-six obese young women (body fat percentage ≥ 30) received either SIT (n=16), HIIT (n=16), or no training (n=14), 3-4 sessions per week, for 12 weeks. The abdominal visceral fat area (AVFA) and abdominal subcutaneous fat area (ASFA) of the participants were measured through computed tomography scans pre-intervention and post-intervention. Total fat mass and the fat mass of the android, gynoid, and trunk regions were assessed through dual-energy X-ray absorptiometry. Results: Following the intervention, abdominal visceral and subcutaneous fat were reduced markedly (p<0.05). The reduction in AVFA (-6.31, -9.7 cm2) was not different between SIT and HIIT (p>0.05), while the reduction in ASFA (-17.4, -40.7 cm2) in SIT was less than that in HIIT (p<0.05). Less reduction in the fat mass of the trunk (-1.2, -2.0 kg) region was also found in SIT, while the reductions in fat percentage (-1.9%, -2.0%), total fat mass (-2.0, -2.8 kg), and fat mass of the android (-0.2, -0.2 kg), and gynoid (-0.4, -0.3 kg) regions did not differ between the two regimes (p>0.05). In contrast, the increase in V̇O2max was significant greater following the SIT than HIIT (p<0.01). No variable changed in CON. Conclusions: Such findings suggest that the lower training load and exercise time commitments of the SIT regime could optimize the time-efficiency advantage of the traditional HIIT, facilitating the abdominal visceral fat reduction in obese young women.